￼The aesthetic experience as a characteristic ￼feature of brain dynamics - Giuseppe Vitiello (Aisthesis, 2015)
The brain constructs within itself an understanding of its surround which constitutes its own world. This is described as its Double in the frame of the dissipative quantum model of brain, where the perception-action arc in the Merleau-Ponty’s phenomenology of perception finds its formal description. In the dialog with the Double, the continuous attempt to reach the equilibrium shows that the real goal pursued by the brain activity is the aesthetical experience, the most harmonious “to-be-in-the-world” reached through reciprocal actions, the aesthetical dimension characterized by the “pleasure” of the perception. Aesthetical pleasure unavoidably implies disclosure, to manifest “signs”, artistic communication. An interpersonal, collective level of consciousness then arises, a larger stage where the actors are mutually dependent. The coherent structure of the brain background state manifests itself in the auto-similarity properties of fractal structures. These are observed to occur also in a large number of natural phenomena and systems. The conception of Nature divided in separated domains is replaced by the vision of Nature unified by laws of form implied by the underlying quantum dynamics of the coherent vacuum, an integrated ecological vision.